A 12-Week Multi-Modal Exercise Program: Feasibility of Combined Exercise and Simplified 8-Style Tai Chi Following Lung Cancer Surgery. (August 2020) - Lu, Ting; Denehy, Linda; Cao, Yuejiao; Cong, Qirui; Wu, En; Granger, Catherine L.; Ni, Jun; Edbrooke, Lara
Objective: To assess the feasibility, safety, and preliminary effect of a 12-week multi-modal rehabilitation program targeted at improving health-related quality of life and physical activity levels of patients with lung cancer following treatment. Methods: Patients with stage I to IIIA non-small cell lung cancer were included 6 to 12 weeks following completion of treatment. The intervention comprised of aerobic exercise (brisk walking), resistance training and 8-style Tai Chi. The 12-week program included 2 supervised center-based sessions per week of 90 minutes duration and home-based exercise. The primary outcomes were the feasibility and safety of the intervention. Secondary outcomes (assessed pre and post program) were physical and patient-reported outcomes. Results: Seventy-eight patients were approached during the 6-month recruitment period and 17 (22%) consented to the study. Eight participants (47%) met the definition of adherence to the program (attending at least 70% of supervised sessions). No serious adverse events occurred. A significant reduction in anxiety and depression was observed post-program. In addition, improvements in respiratory function, sleep quality, and some health-related quality of life domains were observed post-program. There were no significant differences in functional capacity or physical activity levels. Conclusion: This multi-modal exercise training program was safe, although the feasibility of the program in its current state is not supported given the low consent rate and low adherence to the intervention.